The Impact of the STEM-Integrated Learning Model on Students' Academic Achievement and Attitudes Towards Science Courses - Ümmügülsüm Altun; Ümit Şimşek (Educational Academic Research)
This study examines the effects of integrating STEM activities into the science curriculum on students’ academic achievement in the circulatory system topic and their attitudes toward science. This study was designed as a quantitative research and implemented using a pretest–posttest control group quasi-experimental design. This design is commonly employed in experimental research, as it s considered to provide a means to establish valid causal relationships through the control of extraneous variables. The study sample consisted of 40 sixth-grade students (Experimental group = 20 Control group = 20) from a middle school in Erzurum province during the 2022–2023 academic year. In the study, the Circulatory System Academic Achievement Test (CSAT) and the Attitude Scale Toward Science Course (ASSC) were employed to assess students' academic achievement and attitudes toward the science course. Following data collection, statistical analyses were conducted to examine group differences. T-tests, one-way analysis of variance (ANOVA), and analysis of covariance (ANCOVA) were conducted. Based on the analysis results, the derived findings were systematically organized into tables and subsequently interpreted in a comprehensive manner. An effect size was also calculated for the ASSC. The research findings indicate a statistically significant difference in academic achievement between the experimental and control groups, favoring the experimental group. However, no statistically significant difference was observed in students' attitudes toward the science course.